Penerapan Pajak Kendaraan Bermotor terhadap Kendaraan Bernomor Polisi Luar Wilayah Bali - I Gede Ivan Wahyu Pramana; Ida Ayu Putu Widiati; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
Seeing the number of vehicles with police numbers outside the area operating in Bali, in the Bali Provincial Regulation No. 4 of 2016 concerning the Implementation of Traffic and Public Transportation it is explained that vehicles from outside the Bali area can only be in Bali for 3 consecutive months if they exceed that time. then must do Transfer of Name Duty. This research is formulated to determine the imposition of motor vehicle tax in Bali Province, and to determine the intensification of motor vehicle tax imposition on police numbered vehicles from outside Bali. This research uses empirical law research type. The results of this study indicate that the collection of Motor Vehicle Tax in Bali Province can be carried out by taxpayers by following the procedures for implementing Motor Vehicle Tax collection as contained in the Regional Regulation of the Province of Bali Number 1 of 2011 concerning Regional Taxes. Regarding vehicles with police numbers outside the Bali Region, they cannot be taxed because there are no regulations governing these vehicles. This has also led the Bali Provincial Government to plan several efforts for vehicles outside the Bali region that have passed the time to reverse name.